Madagascar 2015 Review of Public Expenditure in Social Sectors : Executive Summary - World Bank (Washington, DC, 2016)
Madagascar’s economic growth has been slow at 1 percent annually in the last five years and far inferior to sub-Saharan region’s average. Income per capita in 2014 fell to around USD 400 (2005 constant USD), losing about 20 percent from 1970 when per capita income reached the highest point since independence. The economic and social effects of the 2009 political crisis were intensified by the suspension of many donor activities which, in a country where international aid represented 40 percent of the government budget, led to significant cuts in investments and a sharp decline in the delivery of services. Macroeconomic stability was maintained during the crisis, as both fiscal and monetary authorities maintained prudent policies. A low public debt to GDP ratio (37.3 percent in 2014) and a low tax revenue (9.7 percent of GDP in 2014) contributed to hindering public investments necessary for development and adequate provision of public services. In a context of high poverty rates, low overall public resources to finance public services delivery, and continuous fragility, economic and political instability, how can public spending promote better outcomes in education and health? How can the Government of Madagascar and its partners support better access to improved quality of services, in particular for the most vulnerable? The Review of Public Spending in Social Sectors in Madagascar systematically analyses how education, health and nutrition have been financed over the past five years. It examines the amounts, distribution and impact of public spending, and formulates recommendations on how best to allocate future public spending with a focus on incremental resources.